2022
DOI: 10.3390/cancers14184357
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin and Ivermectin Enhance the Efficacy of Paclitaxel in Chemoresistant High-Grade Serous Carcinoma

Abstract: Chemotherapy is a hallmark in high-grade serous carcinoma management; however, chemoresistance and side effects lead to therapeutic interruption. Combining repurposed drugs with chemotherapy has the potential to improve antineoplastic efficacy, since drugs can have independent mechanisms of action and suppress different pathways simultaneously. This study aimed to explore whether the combination of Paclitaxel with repurposed drugs led to a therapeutic benefit. Thus, we evaluated the cytotoxic effects of Paclit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…The Chou–Talalay method is based on the median effect equation, derived from the principle of the law of mass action. This unified theory encompasses the Michaelis–Menten, Hill, Henderson–Hasselbalch, and Scatchard equations in biochemistry and biophysics and provides a quantitative definition for additive effect (CI = 1), synergism (CI < 1), and antagonism (CI > 1) in drug combinations [ 25 ]. The fractional effect is a value between 0 and 1, where 0 means that the drug did not affect cell viability, and 1 means that the drug had a full effect in decreasing cell viability [ 19 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Chou–Talalay method is based on the median effect equation, derived from the principle of the law of mass action. This unified theory encompasses the Michaelis–Menten, Hill, Henderson–Hasselbalch, and Scatchard equations in biochemistry and biophysics and provides a quantitative definition for additive effect (CI = 1), synergism (CI < 1), and antagonism (CI > 1) in drug combinations [ 25 ]. The fractional effect is a value between 0 and 1, where 0 means that the drug did not affect cell viability, and 1 means that the drug had a full effect in decreasing cell viability [ 19 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another significant limitation of this study is that although all the included studies described the combined use of mushroom extracts with chemotherapeutic agents as synergistic or potentiating, none of them carried out a comprehensive analysis of inhibitory concentrations. For example, there was no adequate investigation into combinations of chemotherapeutic drugs and mushroom extracts using increasing concentrations of both substances in a fixed ratio, as suggested by methods such as the Chou–Talalay approach [ 56 ] and as highlighted in the studies by Duarte et al [ 57 ] and Nunes et al [ 58 ], which used a bioinformatics tool.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we explored the potential for ivermectin to interact synergistically with pitavastatin and potentially reduce the dose of pitavastatin necessary to treat ovarian cancer. Previous work from Ricardo et al has shown a synergistic interaction between pitavastatin, paclitaxel, and ivermectin [ 30 ]. These authors found that these drugs synergistically decreased the viability of paclitaxel-resistant cells, using several different models to evaluate synergy.…”
Section: Discussionmentioning
confidence: 99%